2021
DOI: 10.1007/s10162-021-00800-8
|View full text |Cite
|
Sign up to set email alerts
|

Reweighting of Binaural Localization Cues Induced by Lateralization Training

Abstract: Normal-hearing listeners adapt to alterations in sound localization cues. This adaptation can result from the establishment of a new spatial map of the altered cues or from a stronger relative weighting of unaltered compared to altered cues. Such reweighting has been shown for monaural vs. binaural cues. However, studies attempting to reweight the two binaural cues, interaural differences in time (ITD) and level (ILD), yielded inconclusive results. This study investigated whether binaural-cue reweighting can b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 50 publications
4
22
1
Order By: Relevance
“…Furthermore, recent studies have demonstrated that lateralization training can lead to a reweighting of binaural cues in normal hearing listeners (Kumpik et al 2019; Klingel et al 2021) and biCI users (Klingel and Laback 2022), such that the listeners rely more or less heavily on ILDs or ITDs respectively depending on which cue is more reliable or informative. This could be relevant for CI listeners, as they could similarly down-weight ITD cues if the ongoing stimulation with clinical processors does not transmit reliable, informative ITDs which would thus encourage a reliance exclusively on ILDs to the detriment of ITDs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have demonstrated that lateralization training can lead to a reweighting of binaural cues in normal hearing listeners (Kumpik et al 2019; Klingel et al 2021) and biCI users (Klingel and Laback 2022), such that the listeners rely more or less heavily on ILDs or ITDs respectively depending on which cue is more reliable or informative. This could be relevant for CI listeners, as they could similarly down-weight ITD cues if the ongoing stimulation with clinical processors does not transmit reliable, informative ITDs which would thus encourage a reliance exclusively on ILDs to the detriment of ITDs.…”
Section: Discussionmentioning
confidence: 99%
“… Klingel et al (2020) also observed an increase in ILD weighting after participants received response feedback consistent with the ILDs of a mid-frequency (2–4 kHz) narrow-band noise stimulus in an auditory discrimination task, but did not test a group receiving feedback consistent with the ITDs. Finally, Klingel et al (2021) observed a comparably strong increase in either the ITD or the ILD weighting of the same 2–4-kHz noise stimulus, depending on which cue was visually reinforced during a lateralization task in a virtual audio-visual environment.…”
Section: Introductionmentioning
confidence: 88%
“…The aim of this experiment was to test whether binaural-cue weights, measured similarly to Macpherson and Middlebrooks (2002) , will show gradual weight changes across different frequency regions or whether they will show divergence for the lowest and highest frequency bands but constant weights in between, similar to the results reported by Ahrens et al (2020) . We further investigated whether binaural-cue reweighting can be induced for different frequency regions using the paradigm of Klingel et al . (2021 ; see description of methods below).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations